MEMBANGUN KESADARAN REMAJA : MENGATASI PERNIKAHAN DINI MELALUI PENDIDIKAN - Isnaini Nurdiah; Mirna Nur Alia Abdullah (SABANA: Jurnal Sosiologi, Antropologi, dan Budaya Nusantara, 2024)
Early marriage is a marriage under the age of the target preparation has not been said to be maximized in terms of physical preparation, mental preparation as well as material preparation. The Law of the Republic of Indonesia No.1 of 1974 regulates that marriage is only permitted if the man has reached the age of 19 years and the woman has reached the age of 16 years. Meanwhile, if based on health science, the ideal age that is biologically and psychologically mature is 20 to 25 years for women, then 25-30 years for men. The purpose of this research is to build adolescents' awareness that to overcome early marriage, it can be through education and also the role of parents is very important in the process of growing children to have a good mindset with education.The method used in this research is a qualitative method with data collection techniques using literature studies.The results showed that adolescents really need education in overcoming early marriage and the role of parents who must facilitate their children's education process so that a child can think critically before acting.